ANALISIS STATISTIK DAN EKONOMETRI DALAM PENELITIAN EKONOMI: KAJIAN PUSTAKA TENTANG PEMILIHAN METODE REGRESI, UJI ASUMSI KLASIK, DAN APLIKASI DATA PANEL PADA STUDI PEMBANGUNAN DAN KETENAGAKERJAAN - Ahmad Rizani; Taufik Udango; Marsida (CV. Lafadz Jaya, 2026)
This article discusses statistical and econometric analysis in economic research through a literature review on the selection of regression methods, tests of classical assumptions, and the application of panel data in development and labour market studies. This review demonstrates that the choice of regression method must be tailored to the characteristics of the data and the research objectives in order to ensure that the results of the analysis are more accurate and reliable. Classical assumption tests play a vital role in ensuring that regression models meet statistical requirements, thereby ensuring that the resulting estimates are valid and efficient. Furthermore, panel data is considered highly relevant in development and labour market research as it is capable of capturing dynamics across regions and over time simultaneously. Based on a review of the existing literature, panel data has been shown to offer greater flexibility in analysing complex and heterogeneous economic phenomena. Consequently, an understanding of regression methods, classical assumption testing, and the use of panel data forms a vital foundation for producing high-quality economic research that is useful for policy formulation.